Mycobacterium goodii pulmonary disease with organizing pneumonia: A case report and review of literature - Yu Shionoya; Hajime Kasai; Reiya Kono; Ryutaro Hirama; Masayuki Ota; Akira Naito; Mitsuhiro Abe; Takeshi Kawasaki; Jun‐ichiro Ikeda; Takuji Suzuki (Respirology Case Reports)
Abstract Mycobacterium goodii, a rapidly growing non‐tuberculous mycobacterium, rarely causes pulmonary diseases. A patient was admitted to our hospital with a fever and cough. Chest radiography revealed consolidation in the right middle lung. As he had previously been treated for organizing pneumonia (OP), he was diagnosed with OP recurrence and administered systemic corticosteroids. Although initial improvement was observed, the pulmonary consolidations worsened. Transbronchial lung cryobiopsy revealed an OP pattern. M. goodii was identified in sputum acid‐fast bacilli cultures. The patient was diagnosed with M. goodii pulmonary disease and secondary OP. Although intravenous imipenem‐cilastatin, amikacin, and ciprofloxacin led to initial improvement in pulmonary consolidations, the consolidations re‐worsened. Systemic corticosteroids were initiated, resulting in improvement in the consolidations. The dose of systemic corticosteroids was tapered; oral antimycobacterial therapy was continued. M. goodii can cause pulmonary disease and induce OP; antimycobacterial therapy and systemic corticosteroids can be effective.